Kaj nam o matematičnem znanju maturantov sporoča raziskava TIMSS Advanced? - Japelj Pavešić, Barbara (Obzornik za matematiko in fiziko, 2017)
The international report of the results of large scale assessments of pre-university mathematics has brought some important new information on mathematics teaching in Slovenia. Most importantly, the knowledge of students who choose the higher level of the national mathematics examination has grown and is relatively high. The paper presents results of the first national analysis. We compare the results of the study with the results from previous assessments: from the first participation of Slovenia in the international comparative study in 1989 and from three studies of trends in the years 1995, 2008 and 2015. The independently measured achievements of TIMSS Advanced were linked with the results of the national matura examination. We tried to find the explanation for differences in achievements by gender that are different in both measurements, even though the content and cognitive structure of the tests are very similar. The important factors which explain achievement variance were found to be students% gender, the choice of the national exam difficulty level, the choice of physics for the optional subject at the national examination, and how much students like to learn mathematics.
Keywords: mednarodna raziskava; poučevanje matematike; srednješolci; TIMSS; znanje matematike